2016
DOI: 10.1021/acssuschemeng.6b00101
|View full text |Cite
|
Sign up to set email alerts
|

Furan Production from Glycoaldehyde over HZSM-5

Abstract: Catalytic fast pyrolysis of biomass over zeolite catalysts results primarily in aromatic (e.g. benzene, toluene, xylene) and olefin products. However, furans are a higher value intermediate for their ability to be readily transformed into gasoline, diesel, and chemicals. Here we investigate possible mechanisms for the coupling of glycoaldehyde, a common product of cellulose pyrolysis, over HZSM-5 for the formation of furans. Experimental measurements of neat glycoaldehyde over a fixed bed of HZSM-5 confirm fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
2
16
0
Order By: Relevance
“…A unit cell was constructed for each zeolite, with each model containing the zeolite's primary channel(s) at its center ( Figure 2). Bonds at the edge of each cell were terminated with hydrosilane groups (Si-H) for H-AEL and H-BEA and hydroxyl groups (Si-O-H) for H-ZSM-5 to be consistent with previous literature [10,64]. In each case, Al was substituted at a single T site.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…A unit cell was constructed for each zeolite, with each model containing the zeolite's primary channel(s) at its center ( Figure 2). Bonds at the edge of each cell were terminated with hydrosilane groups (Si-H) for H-AEL and H-BEA and hydroxyl groups (Si-O-H) for H-ZSM-5 to be consistent with previous literature [10,64]. In each case, Al was substituted at a single T site.…”
Section: Methodssupporting
confidence: 71%
“…The dehydration reactions at lower temperatures are preferable because they remove oxygen without removing carbon, and carbon yield is highly correlated with fuel selling price [8]. Such dehydration reactions are likely to be rate-limiting for a variety of reaction classes, including Diels-Alder cycloaddition and carbon-carbon coupling reactions of carbonyls [9,10]. Hence, an ability to control dehydration kinetics within zeolite pores can be desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the reactive bond length is related to the bond strength in the TS; the stronger the bond strength, the longer is the bond length in its TS. This is also called “late” TS or “early” TS . Hence, the longer length of O–H in TS2 means a more active state of the B–O species as compared with TS1.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This is also called "late" TS or "early" TS. 25 In Figure 6, as mentioned above, TS1 corresponds to the transition state of the first dehydrogenation step based on the molecular adsorption state of O 2 . The relative free energy of TS1 is 116.1 kcal/mol, which means that ΔG a is 79.9 kcal/mol for this elementary reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Glycolaldehyde was shown to yield furans such as furanone below 300 °C, while at >400 °C further reactions to aromatics occurred [37], and general the conversion of model compounds and the yield of aromatics tend to increase with temperature. Chen et al [36] reported a higher yield of coke (~11 C%) and a lower yield of liquid product (9.5 C%) when upgrading acetol over HZSM-5 at 500 °C, with 68% of the liquid products attributed to aromatics (incl.…”
Section: Introductionmentioning
confidence: 99%